Credit Growth and Economic Recovery in Europe After the Global Financial Crisis - Antoshin, Sergei (IMF Working Papers; Working Paper, 2017)
This paper reviews the empirical relationships between credit growth, economic recovery, and bank profitability in Europe after the global financial crisis (GFC). We find that the post-GFC recoveries in Europe have been weaker than previous recoveries, with the 'double-dip' recessions in 2011-12 in many countries and the worldwide reach of the GFC explaining the underperformance. Bank lending has been subdued as well, but this appears to have only held back the recovery relatively moderately. A 10 percent increase in bank credit to the private sector is associated with a rise of 0.6-1 percent in real GDP and 2-2 1\2 percent in real private investment. These relationships have not changed significantly during and after the GFC. Loan quality, customer deposits, bank equity price index, and bank capital appear to be closely linked to bank lending. As expected, bank profitability is positively and significantly influenced by credit growth, but this relationship has weakened after the GFC.